Weighted Composition Operators and Integral-Type Operators between Weighted Hardy Spaces on the Unit Ball - Stevo Stević; Sei-Ichiro Ueki (Discrete Dynamics in Nature and Society)
We study the boundedness and compactness of the weighted composition operators as well as integral-type operators between weighted Hardy spaces on the unit ball.